Intensity-modulated radiotherapy with a multileaf collimator - Curtin-Savard, Arthur J (Radiology and oncology (Ljubljana), 1999)
In intensity-modulated radiation therapy (IMRT), a small number of spatially-modulated beam ports is used to deliver a uniformly high dose to thetarget region, while simultaneously producing a better sparing of normal tissues than is possible with conventional, non-modulated beam delivery. When intensity-modulation is carried out with a multileaf collimator rather than with physical compensators, any required intensity pattern can be produced with a minimal planning effort on the part of the physicist or dosimetrist, and with reduced manipulation on the part of the therapists. The paper describes the recent implementation of multileaf collimator based intensity-modulated radiation therapy at McGill University in Montreal.
Keywords: Methods; Radiotherapy; Radiotherapy dosage; Radiotherapy planning, computer-assisted